Care Centers and Professional Caregivers: from the Project to a Sustainable Social Child Care Policy - Genienė, Rasa; Nedvecka, Jovita (Socialinė teorija, empirija, politika ir praktika, 2021)
In Lithuania the deinstitutionalisation of children left without parental care is being implemented since 2014. The term of transformation is more recognizable in the political context of the country. Various alternative services to institutional care are being developed during the transformation process, but some have become massive and overly institutional in nature (e.g., community children living homes), while the institute of professional caregivers has not gained popular attention when comparing child care rates across different alternatives. This article presents and discusses the activities of care centers that train permanent guardians (caregivers) and professional guardians. The article presents a research during which the staff of the care center evaluated the effectiveness of the activities of the care center and the guardians on duty. The results of the study revealed that care centers face the risk of projectivity at both micro and macro levels. Cooperation and support between the Ministry of Social security and labout and municipalities and other institutions is also very important for the effectiveness of care centers.
Keywords: care center; professional guardian; community children care home; deinstitutionalisation